PENGARUH PENGGUNAAN RUMOH ACEH SEBAGAI SUMBER PEMBELAJARAN GEOGRAFI TERHADAP PEMAHAMAN KONSEP MITIGASI BENCANA - Barona, Cucut Satria; Maryani, Enok; Ruhimat, Mamat (Indonesia University of Education, 2015)
Learning geography in SMA Negeri 1 Peusangan Selatan using local wisdom knowledge as a source of learning has never been applied before. Use of local wisdom knowledge in the topic Rumoh Aceh disaster mitigation is using studytour method and audio visual media of video. Research purposes to analyze the understanding of the concept of disaster mitigation learners grade X through Rumoh Aceh before and after learning by using the studytour method and video in the learning process in SMA Negeri 1 Peusangan Selatan Kabupaten Bireuen. This research uses a type of quantitative research with experimental approach. The population in this research the entire SMA Negeri 1 Peusangan Selatan learners in even-numbered years semester lesson 2014/2015, research sample learners class X IS as much as 48 students by purposive sampling technique.Â Data collection techniques using tests, student worksheets, and question form. Technique of data analysis using statistical test of normality, homogeneity and T-test with the help of SPSS Statistic 21. The results showed that 1) there is a difference in learning outcomes understanding of the concept of disaster mitigation on learners who use Rumoh Aceh as a learning resource by using the studytour method of experiment class before and after the treatment. 2) there is a difference in learning outcomes understanding of the concept of disaster mitigation on learners who use Rumoh Aceh as a learning resource by using the video of control class before and after the treatment. 3) learners responses against learning activities using the studytour method is very good. Implementation of the studytour method have constraints related to preparation and implementation.